DDAH1 promotes neurogenesis and neural repair in cerebral ischemia - Qiming Gao; Pinfei Ni; Yilin Wang; Peiyun Huo; Xiaojie Zhang; Sihan Wang; Fuyao Xiao; Yixuan Li; Wei Feng; Juntao Yuan; Teng Zhang; Qiang Li; et al. (Elsevier, 2024)
Choline acetyltransferase (ChAT)-positive neurons in neural stem cell (NSC) niches can evoke adult neurogenesis (AN) and restore impaired brain function after injury, such as acute ischemic stroke (AIS). However, the relevant mechanism by which ChAT+ neurons develop in NSC niches is poorly understood. Our RNA-seq analysis revealed that dimethylarginine dimethylaminohydrolase 1 (DDAH1), a hydrolase for asymmetric NG,NG-dimethylarginine (ADMA), regulated genes responsible for the synthesis and transportation of acetylcholine (ACh) (Chat, Slc5a7 and Slc18a3) after stroke insult. The dual-luciferase reporter assay further suggested that DDAH1 controlled the activity of ChAT, possibly through hypoxia-inducible factor 1α (HIF-1α). KC7F2, an inhibitor of HIF-1α, abolished DDAH1-induced ChAT expression and suppressed neurogenesis. As expected, DDAH1 was clinically elevated in the blood of AIS patients and was positively correlated with AIS severity. By comparing the results among Ddah1 general knockout (KO) mice, transgenic (TG) mice and wild-type (WT) mice, we discovered that DDAH1 upregulated the proliferation and neural differentiation of NSCs in the subgranular zone (SGZ) under ischemic insult. As a result, DDAH1 may promote cognitive and motor function recovery against stroke impairment, while these neuroprotective effects are dramatically suppressed by NSC conditional knockout of Ddah1 in mice.